PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN TAMU MENGINAP DI HOTEL SAHID BATAM CENTER - Rahmadi, Dicky; Hikmah, Hikmah (SCIENTIA JOURNAL, 2021)
Customer satisfaction is a condition in which the wishes, needs and expectations of a customer for a service or product, in the hotel industry, one of the determining factors for customer satisfaction is the quality of service and facilities. Good quality service will make customers happy and comfortable, of course it will encourage customers to always use the service again, then good and adequate facilities will give pleasure to customers who use these facilities. The research objective was to determine the effect of service quality and facilities on customer satisfaction staying at Hotel Sahid Batam Center, either partially or simultaneously. Population for this study were guests who stayed at Hotel Sahid Batam Center. The variables used in this study are service quality (X1), facilities (X2) and customer satisfaction (Y). Sampling used nonprobability sampling technique, which usedmethod incidental sampling, so that sample obtained was 149 samples. The method of analyzing data usesmultiple linear regression analysis method with SPSS25. The results of this studyindicate that service quality partially has a significant positive effect oncustomer satisfaction, then facilities partially have a significant positiv eeffect on customer satisfaction. Well as service quality and facilities simultaneously have a significant positive effect on customer satisfaction